2020
DOI: 10.1177/1028315320963508
|View full text |Cite
|
Sign up to set email alerts
|

Faculty International Engagement: Examining Rationales, Strategies, and Barriers in Institutional Settings

Abstract: The dramatic expansion of the international dimension in higher education has incited broadened and diverse interpretations of internationalization. As faculty members are integral in achieving many of the expected higher education goals, understanding their perspectives toward internationalization process is critical. Administrative leaders also play a vital role in influencing the conditions of internationalization and working alongside the faculty. Addressing the rationales, strategies, and barriers encount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…This situation also appears similar to being employed in public universities, which we found negatively related to IRC and whose numbers are high in newly established institutions (Özoglu et al, 2016). IRC has been approached to legitimize the revenue and reputation-oriented strategies for internationalization in many countries, which may lead to a more segregated and unequal HE globally (Calikoglu et al, 2020;de Wit, 2019). Our study has demonstrated that this risk should also be borne in mind for Turkish HE.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This situation also appears similar to being employed in public universities, which we found negatively related to IRC and whose numbers are high in newly established institutions (Özoglu et al, 2016). IRC has been approached to legitimize the revenue and reputation-oriented strategies for internationalization in many countries, which may lead to a more segregated and unequal HE globally (Calikoglu et al, 2020;de Wit, 2019). Our study has demonstrated that this risk should also be borne in mind for Turkish HE.…”
Section: Discussionmentioning
confidence: 82%
“…The results reveal that professional factors significantly related to IRC include the academic title and a doctoral degree obtained abroad and an orientation towards research that is especially multidisciplinary or international in scope. The importance of gaining a graduate degree abroad in academics' involvement in international activities has been discussed by several authors (e.g., Calikoglu, Lee, & Arslan, 2020;Finkelstein & Sethi, 2014). These authors asserted that earning doctoral degree abroad is influential in expanding academics' own international network and institutional international collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…It should be said that the national cultural soft power directly affects the level of comprehensive national power of a country or region, and is also an important basis for its international discourse and the size of national influence. National cultural soft power is the cultural soft power shaped and constructed by national power, and cultural soft power is a derivative concept of "soft power" [5] . Therefore, in order to fully grasp the basic connotation of national cultural soft power, it is necessary to conduct an academic exploration of the genealogy of the knowledge of "soft power" and "cultural soft power" and other related concepts.…”
Section: Basic Connotation Of Cultural Soft Powermentioning
confidence: 99%
“…Meanwhile, diversity proves a broad, partly invisible concept, including gender, age, backgrounds in research and education, social dimensions, experiences, and personalities ( Van den Hende et al, 2023b). The meaning and implications of diversity depend on the specific level and type of diversity and various contextual factors (Agnew, 2012;Green & Whitsed, 2015;Laufer, 2021;Calikoglu et al, 2022;Van den Hende & Riezebos, 2023;Zadravec & Kocar, 2023;Zou et al, 2023). The paradox is that more diversity empowers creativity and innovation, yet it also divides people into smaller cooperative groups (Schimmelpfennig et al, 2022).…”
Section: Duality Four: Establishing Mutual Understanding and Shared G...mentioning
confidence: 99%
“…Hence, as these scholars urge, organisations must do more to establish trust and enable stakeholders to communicate, coordinate, and work together for mutual benefits, while staff and students must learn to handle their colleagues' and fellow students' diverse backgrounds and perspectives. For example, Calikoglu et al (2022) propose specific strategies for institutional communication and support, encouraging adaptive leadership and flexible teaching schedules.…”
Section: Duality Four: Establishing Mutual Understanding and Shared G...mentioning
confidence: 99%